Iron-Rich Conditions Induce OmpA and Virulence Changes of Acinetobacter baumannii - Liu, Hui; Cao, Chun yuan; Qiu, Fu lan; Huang, Hao Nan; Xie, Hongyan; Dong, Renkang; Shi, Yu Zhen; Hu, Xiu Nian (Frontiers in Microbiology, 2021)
Background: Iron ions affect the expression of outer membrane protein A (OmpA), a major pathogenic protein in Acinetobacter baumannii. Objective: To analyze the effect of iron ions on the expression of the OmpA protein of A. baumannii and explore its association with the virulence of OmpA. Methods: Site-directed mutagenesis was used to construct ompA gene deletion strains and gene repair strains. The OmpA protein expression of A. baumannii under culture with different contents of iron ions was detected. The virulence of A. baumannii with different OmpA protein expression levels were evaluated in macrophages and mice. Results:OmpA protein levels of the three strains were enhanced under iron-rich conditions. They were reduced in the presence of the iron-chelating agent 2,2'-bipyridine. A. baumannii wild type and +ompA had a remarkable toxic effect on RAW246.7 macrophages (P<0.05). In contrast, the ΔompA had a significantly reduced toxic effect on RAW246.7 macrophages (P<0.05). The levels of the inflammatory factors IL-1β, IL-6, IL-8, and TNFα in the mice spleen were significantly increased in the +ompA strain treatment group compared with the ΔompA strain group (all P<0.05). In addition, the levels were higher in the presence of iron ions than in the presence of the chelating agent. Conclusion: Iron-rich conditions increase the OmpA protein expression of A. baumannii. Strains with high OmpA protein expression were more invasive, which may be a key determinant of A. baumannii infection and pathogenicity. Iron control strategies might be used for the management of A. baumannii.